Experimental and numerical investigation on shot peening of low alloy steel - Pham, Quang Trung (2018)
While shot peening is a well-established technique used in applications where compressive stresses need to be imparted to the material to improve fatigue life, there is still very little fundamental research published. To many, the process is considered to be an art rather than a science. This research aims to investigate the effects of the shot peening process parameters on the surface topography and properties of low alloy steel. The shot peening process influences both the surface and subsurface of the target material with the latter being considered beneficial while the former detrimental. The fatigue life of the material is generally improved by inducing compressive residual stresses into the material subsurface. The process of inducing compressive stresses relies on the impact of high velocity shot onto the target material surface. The impact of these shots tends to make the surface rougher and results in the formation of local stress concentrations which can be a precursor to fatigue failure. Coverage is a major parameter of shot peening process, which is defined as the percentage of the sum of peened area over the total area on the surface of the specimen. A new method with the aid of MatlabTM code to estimate the full coverage for simulation of the shot peening process is proposed in this work. Then, a three dimensional FEM model of the shot peening process was further developed using experimental results for increased accuracy. The numerical and experimental studies give a good agreement in the compared results in the topography and surface roughness of the shot peened steel. As a result, after validating the FEM model with the experimental results, the FEM model can be used to predict the results for the other shot peening conditions (same material) as well as provide the initial operating parameters to reduce the trial and error experimental process. The fatigue tests revealed that the shot peening process could significantly enhance the fatigue life of the treated components. However, a side effect of the process was an increase in surface roughness which was more prevalent under higher peening pressures and led to a reduction in the fatigue life. Therefore, to maximize the performance of the process, the peening parameters need to be carefully selected. Microstructure analysis of the shot peened parts indicated that the nucleation cracks or initiation cracks occurred in the subsurface at depths of 10 to 20 microns in the case of as-received samples but moved up to the free surface for the shot peened parts.